Influence of type traits on stayability in the Ital- ian Mediterranean buffalo - Damiano Altieri; Stefano Biffani; Mayra Gómez; Yuri Gombia; Dario Rossi; Luca Gubitosi; Nadia Piscopo; Francesca Carnovale; Rossella Di Palo (Revista Científica)
The selection schemes adopted over the past 20 years for the Italian Mediterranean Buffalo, together with the marked improvement in farm management techniques and the systematic application of AI in an increasing number of subjects, have resulted in a sharp improvement in the quantities of milk produced per lactation. Experiences from dairy cows suggest that such an improvement could reduce the average productive life span of breeding females and, therefore, their longevity. Animal longevity has a multifactorial etiology where physiology and morphology, in close correlation with each other, cross their effects to enable animals to continue to produce efficiently on the farm. In the past, the selection of the Italian Mediterranean buffalo has mainly focused on increasing milk production, which has had an unfavorable impact on the average farm life of the IMB. This trend needs to be reversed as this inevitably leads to an increase in production costs due to the increase in the replacement rate. There are many ways to assess longevity, both quantitatively, such as age at culling and parity at culling, and qualitatively, such as in the case of stayability, where it is evaluated as a binary variable where 1 and 0 indicate the ability to stay or be culled at a given time, respectively. In a recent study, we evaluated the genetic aspects of stayability in IMB, and the results suggest the possibility of using it in the selection process. This study aimed to correlate stayability with the linear type traits measured by the ANASB for IMB and with the merit score values for body conformation, limbs, feet, and udder. Data from 276.415 buffalo cows registered in the ANASB studbook starting from 1989 were extracted and merged with the official milk test-day recording datasets from the Italian Breeder’s Association (AIA). The stayability from parity one up to 10 was assessed assigning a value of 1 if a calving date was present or 0 otherwise. Investigating the relationship between some morphological traits and longevity would give them the proper em-phasis in formulating genetic indexes or creating specific aggregated indexes to make the selection process more efficient.